Primary tracheobronchial amyloidosis associated with tracheobronchomegaly evaluated by novel four‐dimensional functional CT. Issue 4 (6th November 2015) - Uddin, A.K.M. Nizam; Mansfield, Darren R.; Farmer, Michael W.; Lau, Kenneth K.
Abstract: Amyloid is a heterogeneous family of extracellular proteinaceous deposits characterized by apple‐green birefringence on polarized light microscopy. There are rare case reports of these extracellular deposits accumulating in the upper and central airways. Progressive infiltration may impair glottic and airway function with some cases requiring intervention to improve flow. Bronchoscopy and lung function testing provide dynamic information to monitor for disease progression; however, the recent development of 320 multislice computed tomography (320 CT) enables dynamic, four‐dimensional (4‐D) evaluation of laryngeal and tracheal structure and function and presents as a noninvasive, low‐radiation dose surveillance tool. We reviewed a 43‐year‐old man with primary amyloidosis of the larynx and central airways who presented with an 18‐year history of progressive dysphonia without breathlessness and preserved lung function. 4‐D CT demonstrated marked thickening of supraglottic folds and trachea with marked tracheal dilatation. Despite gross structural abnormalities, dynamic function assessed throughout inspiration and expiration was normal, demonstrating neither rigidity nor dynamic collapse. This combination of structural and functional assessment of the proximal airway by 4‐D CT is a novel application to surveillance for laryngeal and tracheal amyloid. Abstract : Tracheobronchial amyloidosis is a very rare disorder. To our knowledge, this is the first report of Tracheobronchomegaly in primary amyloidosis and the use of 4D CT in dynamic airway assessment for this condition. Despite Tracheobronchomegaly and very irregular and diffuse amyloid wall infiltration, there has been no functional disorder on the CT or abnormal spirometry result. These indicate a favorable prognostic outcome, as shown in our patient who has had this condition for 18 years.